Pengembangan Buku Ajar PKn Talking Pop-Art Book Untuk Meningkatkan Hasil Belajar Kognitif Siswa SD Kelas IV Pada Materi Globalisasi - Feri Tirtoni; Rugaya Meis (Widyagogik, 2018)
ABSTRACT The purpose of this study is the development of learning tools and the textbooks of Civics Education for the fourth grader of elementary school to improve students' cognitive learning outcomes, namely talking pop art book. The design of this book a Civic book contains interesting layout materials with a varied pop art display. This type of research is a developmental study using the Dick and Carey Development model. The subjects of this study were 18 students in the fourth grade of elementary school students at Muhammadiyah 1 Taman Sepanjang. The result of the research was the average score of the students were interested on the implementation of learning strategy particularly Contextual Learning assisted by the Civics Education talking pop art book on the activity of Test I, the result was three components with good category, Attention (average score 4.1, Convidence (confidence) average score 4.2, and Satisfaction (satisfaction) average score 4.33, and components Relevance (relevance) with very good category, with an average score of 4.6. In the second trial, the students were more enthusiastic and motivated with the developed Civics Education Students Books based on Pop Art Book, the students can interact with the book  well and then can further explore their understanding related to the content. Keyword : development of learning tools Civics text book with talking pop art book, cognitive learning outcomes.   ABSTRAKTujuan penelitian ini adalah pengembangan yang dilakukan pada perangkat pembelajaran dan buku ajar PKn kelas IV SD untuk meningkatkan hasil belajar kognitif siswa, yaitu sebuah  perangkat pembelajaran dan buku ajar PKn talking pop art book (sebuah desain buku PKn yang dilengkapi dengan sebuah  layout  materi yang menarik dengan sebuah tampilan  pop art variatif). Jenis penelitian ini merupakan sebuah penelitian pengembangan menggunakan model Pengembangan Dick and Carey. Subyek penelitian adalah siswa kelas IV SD Muhammadiyah 1 Taman Sepanjang sebanyak 18 siswa.Hasil penelitian adalah skor rata-rata minat siswa terhadap penerapan pembelajaran strategi Contextual Learning berbantu buku PKn talking pop art book pada kegiatan Uji Coba I, diperoleh hasil yaitu tiga komponen dengan kategori baik yaitu, Attention (perhatian) skor rata-rata 4.1, Convidence (keyakinan) skor rata-rata 4.2, dan Satisfaction (kepuasan) skor rata-rata 4.33, serta komponen Relevance (keterkaitan) dengan kategori sangat baik, dengan skor rata-rata 4.6. Pada uji coba ke II siswa lebih antusias dan termotifasi dengan Buku Ajar Siswa PKn SD berbasis Pop Art Book  siswa lebih bisa bisa berinteraksi dengan baik dengan buku tersebut dan kemudian bisa lebih mengeksplor pemahamannya terkait materi